Analisis Break Even Point Sebagai Alat Bantu Dalam Perencanaan Laba Pada CV. Madina Murni - Jhon Lenon; Isnaini Harahap; Rahmat Daim Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This type of research is qualitative research. The research period is 3 years, namely 2019 – 2021. The research location is at CV. Madina Murni is located in Mandailing Natal Regency, North Sumatra Province. The type of data used is primary data in the form of interviews and secondary data in the form of sales reports and income reports obtained from CV. Pure Madina. Based on the research that has been carried out, it can be seen that Break Even Point Analysis is intended as a tool for profit planning on CV. Pure Madina. The data analysis used is break even point analysis, which collects data from the company including cost data, income data and sales data. Data collection was carried out using documentation, interviews and observation. Then classify costs, calculate contribution margin, contribution margin ratio, break even point, margin of safety (security level), profit planning analysis and determine profit targets. The results of the research carried out show that break even point analysis can be used as a tool for planning future profits, in accordance with the break even point calculations that have been carried out in 2019, 2020 and 2021. Where the profit planning in 2020 for the 19 L water size is below the profit planning calculation, then for the 600 ML size there is no increase or decrease or is in a break-even condition, and for the 220 ML size, the same as the 19 L size is below the profit planning calculation. the author did. Furthermore, for 2021, the water size of 19 L is the same as the previous year, which is below the profit planning calculation, while for the water size of 600 ML and 220 ML it is already above the planning calculation carried out by the author.